Nowogrodzkie gramoty brzozowe jako najstarsze bałtyckofińskie zabytki językowe - Wojan, Katarzyna (Przegląd Rusycystyczny, 2013)
Katarzyna Wojan Uniwersytet Gdański, Gdańsk, Poland finkf@unigda.pl НОВГОРОДСКИЕ БЕРЕСТЯНЫЕ ГРАМОТЫ КАК ДРЕВНЕЙШИЕ ПРИБАЛТИЙСКО-ФИНСКИЕ ПАМЯТНИКИ ПИСЬМЕННОСТИ Резюме Настоящая статья содержит краткий очерк древнейших памятников прибалтийских финнов — т.н. новгородких грамот на берестяной коре, восходящих к XI–XIII вв. Самый старый из известных памятников на западнофинском (старокарельском) этнолекте — это березовая грамота № 292, датируемая 1238–1268 годами, написанная кириллицей с элементами рунических знаков. Она представляет собой, состоящую из четырех стихов, языческую запись заговора от грома (молнии) либо молитвы. Автор описывает ключевые лингвистические проблемы (на уровне графики, семантики, грамматики, языковой интерференции), связанные с декодированием данной грамоты. Подчеркивает большое влияние живых прибалтийско-финских языков/диалектов, а также финно-угорского субстрата на древненовгородкий диалект. Карельские грамоты на бересте свидетельствуют о непосредственных культурно-языковых и общественных контактах и трансфертах многих групп западных финнов с новгородскими славянами. BIRCH BARK WRITINGS OF NOVGOROD AS THE OLDEST BALTO-FINNIC TEXTS SummaryThe article gives a brief description of the oldest Balto-Finnic texts, i.e. the Novgorod birch bark writings dating from the 11th–13th centuries. The oldest medieval Baltic Finnic writing is the birch bark text No 292 dating back to 1238–1268 and rendering the Old Karelian ethnolect in Cyrillic. It consists of four verses of pagan incantation or beseeching prayer to thunderbolt (lightning). The author of the article presents central linguistic problems associated with the decoding of those texts (on the level of graphs, semantics, grammar and linguistic interference). Further on, the article demonstrates the strong influence of the existing Baltic Finnic ethnolects on the Old Novgorod dialect. The Karelian birch bark writings attest to direct contacts and to linguistic, cultural and social transfers between many groups of Western Finns and the Slavs of Novgorod.